Presenting the Model of the Current and Desirable State of the Family Economics Curriculum in the Second Level of High School in Iran - Seyed Ali Hosseini; Abbas Gholtash; Mokhtar Ranjbar (Iranian Journal of Educational Research)
Objective: The aim of this study was to construct a model delineating the existing and preferred configuration of the family economics curriculum at the secondary level of high schools in Iran. Methods: The qualitative segment of the study adhered to grounded theory, while the quantitative aspect adopted a descriptive survey approach. The study participants comprised experts within the field, selected through non-random sampling techniques such as the snowball method. Semi-structured interviews were conducted until reaching theoretical data saturation, involving 30 individuals. In the quantitative phase, a researcher-developed questionnaire was utilized to assess the current and desirable states of the family economics curriculum model. Experts were sampled using a simple random method, resulting in a sample size of 118 participants. Results: The outcomes indicated that the various dimensions and components of family economics education for students encompassed family education, individual factors, societal economic perspectives, social influences, appropriate educational content for enhanced comprehension of economic principles, conducive learning environments, life skills, and pedagogical approaches to economic concepts. Conclusions: In conclusion, the prevailing condition of the family economics curriculum at the secondary level of high schools in Iran demonstrated a positive status.